Pelatihan Ecobrick Sebagai Solusi Kreatif Pengolahan Sampah Plastik Di Lingkungan Kampus Universitas Merangin - Putri Febriani, Widia; Ramahdan, Gion; Sasgita, Nabila; Satria, Deni; Naimah, Naimah; Taradipa, Maharani; Julianto, Tegar; Reynaldi, Reynaldi (Vox Populi: Jurnal Umum Pengabdian Kepada Masyarakat, 2025)
Plastic waste is one of the most pressing environmental issues in Indonesia. Plastic is included in the category of non-organic waste that is very difficult to decompose, because it is made of non-renewable chemicals. In the campus environment, the high volume of plastic waste is getting worse because many food vendors still use plastic as packaging, and accompanied by a low level of student understanding of organic and non-organic waste sorting techniques. The increasing amount of plastic waste will certainly have a negative impact on the environment. One approach that can be applied to reduce plastic waste in the environment is through the 3R concept (Reduce, Reuse, Recycle). One form of the 3R concept is Ecobrick. The purpose of this Ecobrick training is as a creative solution for managing plastic waste in the Merangin University campus environment. This community service activity involved students of the Biology Study Program, Faculty of Science and Technology and students of the Biology Education Study Program, Faculty of Teacher Training and Education, Merangin University. The method used is a participatory approach consisting of 3 stages: preparation, implementation (socialization and counseling) and the final stage. The results obtained are that this Ecobrick-making training has a direct positive impact on the campus environment, increasing students' knowledge in managing inorganic waste with Ecobricks and forming students' habits of disposing of waste in the correct place and caring for the environment. Furthermore, through training and direct practice of Ecobrick-making not only enhances students' creativity. Students' active involvement in processing plastic waste into useful products such as chairs, tables, shelves and flower pots thus raises awareness that plastic waste can be processed into something of high value.